2020
DOI: 10.1002/lio2.499
|View full text |Cite
|
Sign up to set email alerts
|

The minimum effective dose of abobotulinum toxin A injection for allergic rhinitis: A dose‐escalation randomized controlled trial

Abstract: Objective To find the lowest effective injection dose of abobotulinum toxin A (Dysport) for allergic rhinitis. Study Design Dose‐escalation randomized controlled trial. Methods We included all patients aged 18 years or older who had persistent allergic rhinitis and positive allergy skin prick test. The patients were randomly allocated to receive 40, 30, or 20 U of abobotulinum toxin A by injection at the inferior turbinate. We followed up on patients for 12 weeks to evaluate nasal symptoms, ocular symptoms, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…[ 25 ] Recent studies also revealed that botulinum toxin reduced MC activity. [ 26 ] Notably, rhinitis and HTS could be treated by the same treatment modality, and this effect may be MC-related. Since ITH is considered a result of remodeling in chronic rhinitis and because of the common features in their pathogenesis and treatment modalities, we investigated the association of ITH and HTS in patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Recent studies also revealed that botulinum toxin reduced MC activity. [ 26 ] Notably, rhinitis and HTS could be treated by the same treatment modality, and this effect may be MC-related. Since ITH is considered a result of remodeling in chronic rhinitis and because of the common features in their pathogenesis and treatment modalities, we investigated the association of ITH and HTS in patients.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 study in which patients were randomly allocated to receive injections of 40, 30, or 20 units of BT-A in the inferior turbinates showed that nasal congestion, runny nose, sneezing, and loss of smell were significantly improved with 40 units; nasal congestion, sneezing, and loss of smell improved with 30 units; and only nasal congestion and loss of smell improved with 20 units 16…”
Section: Dose and Administration Methods Remain Uncertainmentioning
confidence: 99%
“…IT surgery via energy‐related techniques 2304–2363 and via direct tissue removal 1093,2296,2299,2303,2307,2310,2331,2332,2335,2336,2338,2344,2364–2376 have both been extensively studied, with reported high efficacy in reducing symptoms and increasing nasal volume and airflow with minimal complications. Of note, botulinum toxin injection 2377–2379 and high‐intensity focused ultrasound may also provide symptomatic relief, 2380,2381 though there remains limited evidence for their utility. As such, the current literature suggests that, in the properly selected AR patient with concomitant IT hypertrophy, IT surgery is an effective and safe treatment to reduce symptoms and improve QOL.…”
Section: Managementmentioning
confidence: 99%